Political Encounters - Brown, Ruairidh J. author. aut Link
XI, 213 p. 1 illus.
Keywords: This book takes the novel approach of framing Political Obligation as a situation rather than a problem. By doing so, Political Obligation is not considered as an issue to be solved, but a central condition of existence to be investigated and understood. The book launches a hermeneutic inquiry into how this relationship of obligation is constructed through encounters in which the citizen comes face-to-face with the existential manifestations of the State. The book first discusses the dominant approaches to Political Obligation to elucidate the benefits of an existential hermeneutical approach. The notion of encounter is then developed into a hermeneutic approach capable of uncovering and interpreting the arguments, ideas, and narratives of obligation as are communicated in political communities. Finally, the limitations of this approach are considered in reference to the concerns of the Post-truth era. .